A Murine Model With JAK2V617F Expression in Both Hematopoietic Cells and Vascular Endothelial Cells Recapitulates the Key Features of Human Myeloproliferative Neoplasm - Zhang, Haotian; Yeware, Amar; Lee, Sandy; Zhan, Huichun (Frontiers in Oncology, 2021)
The myeloproliferative neoplasms (MPNs) are characterized by an expansion of the neoplastic hematopoietic stem/progenitor cells (HSPC) and an increased risk of cardiovascular complications. The acquired kinase mutation JAK2V617F is present in hematopoietic cells in a majority of patients with MPNs. Vascular endothelial cells (ECs) carrying the JAK2V617F mutation can also be detected in patients with MPNs. In this study, we show that a murine model with both JAK2V617F-bearing hematopoietic cells and JAK2V617F-bearing vascular ECs recapitulated all the key features of the human MPN disease, which include disease transformation from essential thrombocythemia to myelofibrosis, extramedullary splenic hematopoiesis, and spontaneous cardiovascular complications. We also found that, during aging and MPN disease progression, there was a loss of both HSPC number and HSPC function in the marrow while the neoplastic hematopoiesis was relatively maintained in the spleen, mimicking the advanced phases of human MPN disease. Different vascular niche of the marrow and spleen could contribute to the different JAK2V617F mutant stem cell functions we have observed in this JAK2V617F-positive murine model. These results indicate that the spleen is functionally important for the JAK2V617F mutant neoplastic hematopoiesis during aging and MPN disease progression. Compared to other MPN murine models reported so far, our studies demonstrate that JAK2V617F-bearing vascular ECs play an important role in both the hematologic and cardiovascular abnormalities of MPN.